Effect of postoperative residual astigmatism on visual outcomes after trifocal intraocular lens implantation - Zhang, Limei; Shen, Wenqian; Shen, Jiying; Wang, Min; Ni, Shuang; Guo, Haike; Yang, Jin (Frontiers in Medicine, 2023)
To evaluate the effect of residual astigmatism on postoperative visual outcomes after trifocal intraocular lens implantation.In this prospective observational study, we divided 156 eyes into two groups according to postoperative astigmatism measured by subjective optometry and followed them up for 3 months.Visual acuity, modulation transfer function (MTF) curves, Strehl ratio (SR), Visual Function Index-14 scores, and photic phenomena were compared.Results: Linear regression analysis revealed a weak correlation between residual astigmatism and uncorrected distance visual acuity (UDVA) (r=0.190, P=0.016) at 3-month and a significant betweengroup difference in 1 month and 3-month postoperative UDVA (P=0.038, P=0.018, respectively).MTF curve values and SR (MTF-10 total, MTF-10 cornea, MTF-30 total, MTF-30 cornea, SR Total, and SR cornea) were significantly worse (P<0.001), and Visual Function Index-14 scores were lower in the 0.50.05).Postoperative residual astigmatism affects the UDVA of trifocal intraocular lens implanted eyes. Although we found no significant differences in uncorrected intermediate and near visual acuity, both objective and subjective visual quality were affected, suggesting the need for surgical planning when the anticipated postoperative astigmatism is >0.5 D.